Household intention to eliminate mosquito breeding sites following a single-session Geplakkin intervention - Wahyu Naufal; Andri Dwi Hernawan; Elly Trisnawati; Barry Ceasar Octariadi (Universitas Ahmad Dahlan, 2026)
Dengue remains an important public health problem, and household elimination of mosquito breeding sites is central to prevention. Digital technologies may strengthen dengue prevention by integrating health information with vector surveillance, but evidence regarding their relationship with household behavioral intention remains limited. This study evaluated household intention to eliminate mosquito breeding sites following a single-session intervention using the Geplakkin vector surveillance application. A quantitative experiment with a posttest-only control-group design was conducted in Pontianak City, West Kalimantan, Indonesia, from July to October 2025. A total of 320 purposively recruited participants were randomly allocated in a 3:1 ratio to the intervention (n = 240) or control group (n = 80) using a computer-generated sequence. Both groups received routine dengue-prevention education; the intervention group additionally received 15–30 minutes of training on Geplakkin, followed by immediate application use and posttest assessment. Intention was assessed using a Theory of Planned Behavior-based questionnaire. Because scores were not normally distributed, groups were compared using the Mann–Whitney U test. The intervention group had a higher mean intention score than the control group (45.43 ± 4.68 vs 36.73 ± 5.50), with a mean difference of 8.70 points (p < 0.001; effect size = 0.65). Thus, exposure to the single-session Geplakkin intervention was associated with higher immediate intention to eliminate mosquito breeding sites than routine education alone. Longitudinal studies are needed to determine whether this difference is sustained and translates into household vector-control practices.